From Metal Hydrides to Metal Borohydrides - Richter, B.; Grinderslev, J.; Moller, Kasper; Paskevicius, Mark; Jensen, T. (American Chemical Society, 2018)
© 2018 American Chemical Society. Commencing from metal hydrides, versatile synthesis, purification, and desolvation approaches are presented for a wide range of metal borohydrides and their solvates. An optimized and generalized synthesis method is provided for 11 different metal borohydrides, M(BH4)n, (M = Li, Na, Mg, Ca, Sr, Ba, Y, Nd, Sm, Gd, Yb), providing controlled access to more than 15 different polymorphs and in excess of 20 metal borohydride solvate complexes. Commercially unavailable metal hydrides (MHn, M = Sr, Ba, Y, Nd, Sm, Gd, Yb) are synthesized utilizing high pressure hydrogenation. For synthesis of metal borohydrides, all hydrides are mechanochemically activated prior to reaction with dimethylsulfide borane. A purification process is devised, alongside a complementary desolvation process for solvate complexes, yielding high purity products. An array of polymorphically pure metal borohydrides are synthesized in this manner, supporting the general applicability of this method. Additionally, new metal borohydrides, a-, a'- ß-, ?-Yb(BH4)2, a-Nd(BH4)3 and new solvates Sr(BH4)2·1THF, Sm(BH4)2·1THF, Yb(BH4)2·xTHF, x = 1 or 2, Nd(BH4)3·1Me2S, Nd(BH4)3·1.5THF, Sm(BH4)3·1.5THF and Yb(BH4)3·xMe2S ("x" = unspecified), are presented here. Synthesis conditions are optimized individually for each metal, providing insight into reactivity and mechanistic concerns. The reaction follows a nucleophilic addition/hydride-transfer mechanism. Therefore, the reaction is most efficient for ionic and polar-covalent metal hydrides. The presented synthetic approaches are widely applicable, as demonstrated by permitting facile access to a large number of materials and by performing a scale-up synthesis of LiBH4.